A Methodology of Rule Discovery from Large-scale Multi-tier Noisy Educational Data - Yousuf, Tasneem (2018)
A Master of Science thesis in Computer Engineering by Tasneem Yousuf entitled, “A Methodology of Rule Discovery from Large-scale Multi-tier Noisy Educational Data”, submitted in May 2018. Thesis advisor is Dr. Imran Ahmed Zualkernan. Soft and hard copy available.